2004
DOI: 10.3354/meps272257
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural consequences of density-dependent habitat use in juvenile cod Gadus morhua and G. ogac: the role of movement and aggregation

Abstract: Fish behaviour can change to accommodate a variable environment, but changes in behaviour have not been considered in the context of density-dependent habitat use. In Bonavista Bay, Newfoundland, we measured how fish density movement and schooling behaviour changed with habitat in 2 gadids, Atlantic cod Gadus morhua and Greenland cod Gadus ogac, using a combination of field-seines, mark-recapture and laboratory experiments. Density estimates from seines (n = 427) over 5 yr (1996, 1998 to 2001) indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 70 publications
(103 reference statements)
3
45
0
Order By: Relevance
“…Lough (2010) also indicated that limited gravel areas may inhibit the survival of juvenile G. morhua. Juvenile G. morhua density-dependent substrata association was likewise observed by Laurel et al (2004), who found that the abundance of G. morhua was consistently high over seagrass areas and more variable in sand.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Lough (2010) also indicated that limited gravel areas may inhibit the survival of juvenile G. morhua. Juvenile G. morhua density-dependent substrata association was likewise observed by Laurel et al (2004), who found that the abundance of G. morhua was consistently high over seagrass areas and more variable in sand.…”
Section: Discussionmentioning
confidence: 61%
“…However, if these substrata become saturated from increased juvenile gadoid abundance, juveniles may be forced into lower-quality areas where survival is likely to be lower (Morris 1989, 2003, Laurel et al 2004. Equally, areas of higher biodiversity may provide increased food sources in addition to refuge (Sebens 1991, Grat wicke & Speight 2005, Kovalenko et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Massot et al 1994). To date there have been few explicit tests of DDHS in marine fish species (juvenile pollock Pollachius virens, Rangley & Kramer 1998; juvenile cod Gadus morhua and G. ogac, Laurel et al 2004; gag Mycteroperca microlepsis, Lindberg et al 2006) despite the multitude of studies describing area-abundance relationships in marine environments (see Shepherd & Litvak 2004 for review). In flatfish, fine grained sand substrates are preferred over relatively coarser grained substrates (Stoner & Ottmar 2003), most likely because flatfish are more capable of burying in such habitats as a means of reducing predation (Ryer et al 2004; although see Manderson et al 2000) or finding food (Livingston 1987).…”
Section: Density-dependent Habitat Selectionmentioning
confidence: 99%
“…Marshall & Frank 1995, Hutchings 1996, Blanchard et al 2001. Habitat suitability is a dynamic measure mediated by behavior (Laurel et al 2004), ontogeny (e.g. Livingston 1988) and the environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Published accounts of the more extensively studied Atlantic cod describe movements of older individuals over both space and time through mark-recapture methods (Grant & Brown 1998b, Laurel et al 2004, Robichaud & Rose 2004 and acoustic telemetry (Cote et al 2004, Lindholm et al 2007. At the juvenile stage, Greenland cod exhibit demersal habitat use and behaviour similar to juvenile Atlantic cod (e.g.…”
Section: Introductionmentioning
confidence: 99%